Ghana's economic and agricultural transformation: Past performance and future prospects - Xinshen Diao; Peter B. R. Hazell; Shashidhara L. Kolavalli; Danielle Resnick (Oxford University Press, 2019)
Many African countries have experienced unprecedented rates of economic growth in recent years, yet their economic transformations display features that could constrain their future growth prospects. Patterns of urbanization without industrialization, rapid growth of low productivity jobs in the informal economy, and a neglected agricultural sector with increased need for important foods are all areas for concern as Africa continues to develop. Using Ghana as a case study, Ghana's Economic and Agricultural Transformation: Past Performance and Future Prospects integrates economic and political analysis to explore the challenges and opportunities of Africa's transformation. It examines Ghana's overall economic performance since it went through a major Structural Adjustment Program in the early 1980s, and provides an in-depth empirical analysis of the broader economy and the agricultural sector over the last four decades. It explains why Ghana has not transformed its economy more substantially, why its agriculture sector has not played a greater role beyond cocoa production, and what must be done in the future to achieve a successful transformation. In addressing these puzzles Ghana's Economic and Agricultural Transformation considers what the rest of the world can learn from Ghana's experience.
Keywords: 330; agricultural development; governance; economic development; supply chains; economic growth; agricultural research; commodities; urbanization; employment; public expenditure; investment; agroindustrial sector